DYNAMICS OF PSYCHOPATHOLOGICAL SYMPTOMS IN THE POST-COVID-19 PERIOD - Belov, O.O.; Pshuk, N.G.; Skrypnikov, A.M.; Herasymenko, L.O.; Isakov, R.I. (World of Medicine and Biology, 2024)
The dynamics of post-COVID-19 psychopathological manifestations in 31 men and 33 women were studied. It was established that fatigue (75 %), anxiety (70 %), cognitive dysfunction (69 %) and low mood (63 %) dominate the structure. The dynamics of depressive and anxiety changes were more pronounced in the first 6 months (from 63 % to 34 % and from 70 % to 48 %), and fatigue, cognitive impairment and insomnia – after 12 months (from 63 % to 28 %, from 63 % to 23 % and from 33 % to 22 %). In the early period, clinically defined depressive disorders were found in 36 % of patients, in the late period – in 8 %. The prevalence of psychopathological symptoms other than irritability was non-significantly higher among women; they were also found to have higher levels of depression and anxiety. Two years after COVID-19, symptoms of fatigue, cognitive dysfunction, dyssomnia, depression, and anxiety were present in 22 %, 17 %, 16 %, 14 %, and 13 %, respectively. Depression and anxiety rates normalized 12 months after COVID-19, faster in men than in women.
Keywords: COVID-19; post-COVID-19 period; depression; anxiety; fatigue; cognitive dysfunction